Inovasi Motor Listrik Untuk Alat Penggilingan Kacang Tanah - Rifaldi, Rifaldi; Kun Fayakun; Rosalina, Rosalina; Emilia Roza; Ramza, Harry (TIME in Physics, 2023)
This research aims to design a control system for a Peanut Grinder based on a 135 Watt AC Motor, intended to assist small and medium-sized food business entrepreneurs who utilize peanut ingredients. The purpose of this device is to enhance production efficiency in the preparation of peanut-based condiments, replacing the manual and time-consuming process with an automated system capable of sorting peanuts into fine and coarse textures as desired. By utilizing a 135 Watt AC Motor obtained from a washing machine as the main driving component, the design aims to reduce costs by reusing existing components. The control system will encompass mechanisms for grinding peanuts efficiently, ensuring user safety, and regulating motor speed and grinding duration. This research emphasizes environmental friendliness by repurposing unused components. Overall, the proposed Peanut Grinder aims to benefit UMKM entrepreneurs by streamlining production processes and enhancing productivity in the peanut-based condiment preparation.